2016
DOI: 10.1155/2016/7139573
|View full text |Cite
|
Sign up to set email alerts
|

PrimaryHistoplasma capsulatumEnterocolitis Mimicking Peptic and Inflammatory Bowel Disease

Abstract: In immunocompromised patients, histoplasmosis may present as disseminated disease. We present a 52-year-old Caucasian male with symptoms of dyspepsia, postprandial epigastric pain, nausea, and nonbloody diarrhea. Upper and lower gastrointestinal endoscopies were suspicious for inflammatory bowel disease (IBD); however, biopsies were consistent with histoplasmosis, specifically in the duodenum.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(7 citation statements)
references
References 5 publications
0
6
0
1
Order By: Relevance
“…Analysis of the 123 well-documented cases showed the clinical presentation of GIH was often non-specific and mimicked several other gastrointestinal conditions and pathologies, including abdominal tuberculosis (n = 3, 2.4%) [ 85 , 96 , 102 ], GIH and TB coinfection was reported in four [3.3%] cases [ 78 , 87 , 96 , 98 ], inflammatory bowel disease (n = 9, 7.3%) [ 21 , 33 , 40 , 52 , 69 , 75 , 89 , 105 , 107 ], intestinal obstruction (n = 15, 12.2%) [ 15 , 21 , 39 , 50 , 57 , 64 , 71 , 77 , 81 , 89 , 95 , 102 , 103 , 104 , 117 ], abdominal malignancy (n = 9, 7.3%) [ 14 , 16 , 31 , 80 , 83 , 101 , 102 , 108 , 112 ], GI bleeding (n = 29, 23.6%) [ 17 , 18 , 25 , 26 , 27 , 29 , 30 , 31 , 33 , 37 , 41 , 44 , 53 , 56 ,…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Analysis of the 123 well-documented cases showed the clinical presentation of GIH was often non-specific and mimicked several other gastrointestinal conditions and pathologies, including abdominal tuberculosis (n = 3, 2.4%) [ 85 , 96 , 102 ], GIH and TB coinfection was reported in four [3.3%] cases [ 78 , 87 , 96 , 98 ], inflammatory bowel disease (n = 9, 7.3%) [ 21 , 33 , 40 , 52 , 69 , 75 , 89 , 105 , 107 ], intestinal obstruction (n = 15, 12.2%) [ 15 , 21 , 39 , 50 , 57 , 64 , 71 , 77 , 81 , 89 , 95 , 102 , 103 , 104 , 117 ], abdominal malignancy (n = 9, 7.3%) [ 14 , 16 , 31 , 80 , 83 , 101 , 102 , 108 , 112 ], GI bleeding (n = 29, 23.6%) [ 17 , 18 , 25 , 26 , 27 , 29 , 30 , 31 , 33 , 37 , 41 , 44 , 53 , 56 ,…”
Section: Resultsmentioning
confidence: 99%
“…The non-specific signs and symptoms of GIH, as highlighted in this review, include but are not limited to abdominal pain [ 12 , 18 , 19 , 20 , 20 , 21 , 22 , 25 , 27 , 31 , 33 , 35 , 36 , 37 , 38 , 40 , 41 , 43 , 45 , 47 , 50 , 51 , 54 ], diarrhoea [ 12 , 17 , 19 , 21 , 22 , 36 , 37 , 38 , 39 , 40 , 43 , 53 , 68 , 74 , 75 , 103 , 104 , 105 , 106 ], fever [ 12 , 13 , 17 , 19 , 26 , 27 , 28 , 30 , 31 , 33 , 35 ], weight loss [ 13 , 31 , 77 , 79 , 84 , …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However in symptomatic patients, the most common presentation is fever, bloody diarrhea, abdominal pain, hepatosplenomegaly and lymphadenopathy. [5,20] In our case too, abdominal pain, lymphadenopathy and possibly hepato-splenomegaly (abdominal distension) were present. However our patient primarily presented with obstructive features (vomiting, constipation).…”
Section: Discussionmentioning
confidence: 48%
“…These areas serve as potential entry sites for the organisms, which are small, ovoid, usually intracellular yeast forms in macrophages, with small buds at the more pointed pole. [5,3] Appropriate treatment with antifungal therapy definitely improves outcomes; nevertheless, zygomycosis and aspergillosis cases still have high mortality rates. [6] Rachana A et al showed only inflammatory exudate.…”
Section: Introductionmentioning
confidence: 99%